Diklat (Pendidikan dan Latihan): Strategi Peningkatan Kompetensi Komputer Karang Taruna dan Perangkat Desa Sukowuwuh, Purworejo - Suyitno Suyitno (Surya Abdimas, 2019)
The objectives of this community service activity include 1) Implementing and applying Word, PowerPoint, and Excel programs to the community of Sukowuwuh, Bener, Purworejo villages, 2) Knowing the response of youth groups and Sukowuwuh Village Devices, Bener Purworejo. The Target of Community Service is Youth Organization and Sukowuwuh Village Apparatus. In computer training provided using the Sukowuwuh Village Hall. The training material is in the form of computer introduction, word processing using Microsoft Word, making presentations using PowerPoint, and introduction to Excel. The results of the implementation of this activity include: 1) Youth and Village can apply computers for correspondence in Youth and can design home-made food products in Sukowuwuh Village, Bener Sub-District, Purworejo District, 2) Community response is very positive and will apply knowledge owned for purposes in the village and accountant.